Reported Health Benefits of a Vegan Dog Food – A Likert Scale-Type Survey of 100 Guardians - Davies, Mike (Archives of Clinical and Biomedical Research, 2022)
Introduction: There has been a large increase in feeding plant-based foods to pets and advocates extol the health benefits of this practice. However, there is a lack of scientific evidence to support health claims for vegan diets in dogs. Aims: This study aimed to quantify perceived health changes by dog guardians following the feeding of a single brand of UK-produced vegan food for a period of 3 to 12 months. Methods: Dog guardians registered as feeding the vegan food for 3 - 12 months were invited to participate in an online Likert Scale-type survey of observations reflecting health status. Results: 100 guardians completed the survey. The vegan food was acceptable (palatable), and appetite and body weight were not adversely affected. Changes, including improvements, were reported and statistically significant at p< .05 in the following areas: activity, faecal consistency, frequency of defaecation, flatus frequency, flatus antisocial smell, coat glossiness, scales in haircoat (dandruff), redness of the skin (erythema, inflammation), itchiness (scratching; pruritus), and anxiety. Conclusions: This is the first study to quantitatively document guardian reports of apparent specific health benefits associated with feeding a UK vegan dog food. Further prospective, randomised, controlled clinical trials are needed to validate and determine the significance of these observations.